Effect of Dietary Supplementation of Fenugreek Seed (Trigonella Foenum-Graecum L.) Powder on Body weight, Blood-biochemical Parameters and Immunity in Broilers - Kumar, P.; Kumar, S.; Sihag, S.; Sihag, Z.S. (Indian Journal of Animal Nutrition, 2021)
A six-week study was carried out to investigate the effect of dietary supplementation of Fenugreek seeds (Trigonella foenum-graecum L.) powder (FSP) on serological and immunological parameters in broiler chickens. One hundred and forty four day-old chicks were randomly divided into six dietary treatment groups having 24 birds in each group and three replications of 8 birds each. Supplementation with FSP was done at the rate of 0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0% for T1 to T6. The result of the study revealed that there was a significant (p<0.05) decrease in serum total cholesterol and LDL-cholesterol concentrations in the broilers fed diets supplemented with FSP at 1.5% or above. HDL-concentrations were found to be improved significantly (p<0.05) upon FSP supplementation at 1.0% and above. Blood glucose concentration was reduced significantly (p<0.05) as the supplementation of FSP was increased from 1.0% to 3.0%. Expression of genes controlling antibacterial and anti-viral activities revealed that relative mRNA expression of TLR-2 and TLR-7 of broilers was found to be enhanced upon feeding FSP. But a significant down regulation was seen in case of relative mRNA expression of TLR-4 receptors in FSP supplemented groups. Serum triglycerides, SGPT and SGOT concentrations remained unaffected. It was inferred from the study that FSP fenugreek supplementation in the diets of broiler birds have substantial improvement in the serum biochemical parameters along with showing immunological activities.